Long-term outcomes of pediatric hypospadias and surgical intervention - De Win G; Cuckow P; Hoebeke P; Wood D (Dove Medical Press, 2012)
Gunter De Win,1,2 Peter Cuckow,3 Piet Hoebeke,4 Dan Wood21Adolescent and Pediatric Urology, University Hospital, Antwerp, Belgium; 2Adolescent Urology, University College London Hospitals, UK; 3Pediatric Urology, Great Ormond Street Hospital for Sick Children, London, UK; 4Pediatric Urology, University Hospital, Gent, BelgiumAbstract: Hypospadias is one of the most commonly diagnosed male congenital disorders. Many surgical techniques are described and complications often reported include fistula, wound dehiscence, and meatal stenosis. Many surgeons still believe that hypospadias should be surgically corrected before the age of 12 months. However, it is clear that the longer the follow up, the more complications are reported. Correction of a failed hypospadias repair in adult patients can be challenging. While the need for repair of proximal hypospadias during childhood is evident, distal repair during childhood is questionable. Evidence suggests that the psychosexual and functional outcomes of nonoperated distal hypospadias in the adult population are good. Therefore, the benefit of surgery and the burden of complications must be carefully evaluated. This paper highlights the difficulties inherent in decisions related to the assessment of hypospadias, the need for repair, and the paucity of good long-term data.Keywords: hypospadias, chordee, urethroplasty, fistula, stricture, hypospadias complications